Relationship marketing researches in logistics’ organizations: foreign countries experience - Vytautas Juščius; Viktorija Grigaitė (Business: Theory and Practice, 2009)
This paper presents the analysis of foreign researchers’ works which scrutinize relationship marketing, its principles’ adjustment in logistics organizations. Relationship marketing elements identified by different researchers, their influence and importance in relationship with clients in logistics organizations, relationship marketing implementation in business-to-business level are analyzed and compared. It leads to the conclusion that in logistics organizations relationship marketing elements such as trust, specific investments, reputation, information sharing, commitment and cooperation are frequently stressed. Trust has a strong impact on commitment between concerned parties. Trust in logistics service provider increases with specific investments in relationship, information sharing for partnership welfare. Systematized methods, modified relationship marketing schemes are presented.